Simultaneous determination of the novel thiosemicarbazone anti‐cancer agent, Bp4eT, and its main phase I metabolites in plasma: Application to a pilot pharmacokinetic study in rats. (20th November 2013) - Stariat, Ján; Suprunová, Vlasta; Roh, Jaroslav; Šesták, Vít; Eisner, Tomáš; Filipský, Tomáš; Mladěnka, Přemysl; Nobilis, Milan; Šimůnek, Tomáš; Klimeš, Jiří; Kalinowski, Danuta S.; Richardson, Des R.; et al.
ABSTRACT Novel thiosemicarbazone metal chelators are extensively studied anti‐cancer agents with marked and selective activity against a wide variety of cancer cells, as well as human tumor xenografts in mice. This study describes the first validated LC‐MS/MS method for the simultaneous quantification of 2‐benzoylpyridine 4‐ethyl‐3‐thiosemicarbazone (Bp4eT) and its main metabolites (E/Z isomers of the semicarbazone structure, M1‐E and M1‐Z, and the amidrazone metabolite, M2) in plasma. Separation was achieved using a C18 column with ammonium formate/acetonitrile mixture as the mobile phase. Plasma samples were treated using solid‐phase extraction on 96‐well plates. This method was validated over the concentration range of 0.18–2.80 μM for Bp4eT, 0.02–0.37 μM for both M1‐E and M1‐Z, and 0.10–1.60 μM for M2. This methodology was applied to the analysis of samples from in vivo experiments, allowing for the concentration–time profile to be simultaneously assessed for the parent drug and its metabolites. The current study addresses the lack of knowledge regarding the quantitative analysis of thiosemicarbazone anti‐cancer drugs and their metabolites in plasma and provides the first pharmacokinetic data on a lead compound of this class. Copyright © 2013 John Wiley & Sons, Ltd.